Genetic Diversity and Population Structure of Taurine Cattle Using STR Markers in Burkina Faso, West Africa - Tapsoba, A. S. R.; Sawadogo, S. E.; Yougbaré, B.; Traoré, F. G.; Béré, F.; Sanou, M.; Tamboura, H. H.; Bayala, B.; Pichler, R.; Traoré, A.; Periasamy, K. (Faculty of Animal Science, IPB University, 2024)
Burkina Faso relies on its substantial bovine population for meat and milk production, ensuring food security. The country hosts three primary taurine cattle populations: Lobi, Gourounsi Nahouri, and Gourounsi Ténado. These cattle are adapted to local conditions and exhibit valuable trypan tolerant traits, playing a crucial role in sustaining local communities and holding cultural and socio-economic significance. This study aimed to assess the genetic diversity and structure of Burkina’s primary taurine cattle populations using 27 microsatellite markers. Blood samples from 143 cattle representing these populations were genotyped. The analysis included assessing genetic diversity, deviations from Hardy-Weinberg equilibrium, calculating genetic distances, and population structure. The results revealed that all loci were polymorphic, indicating high allelic diversity. The overall mean FIS was moderate (0.028), ranging from -0.36 (CSRM60) to 0.73 (INRA035). Genetic differentiation between populations was moderate, accounting for 4% of the total differences. The highest pairwise FST was observed between Lobi and Gourounsi Ténado. The neighbor-joining tree displayed high admixture levels between Gourounsi populations, while Lobi cattle clustered as a distinct population. The population structure analysis indicated significant zebu gene introgression in Burkina taurine populations with relatively higher levels of admixtures in Gourounsi cattle compared to Lobi. The study provided a thorough genetic analysis of Burkina Faso's taurine cattle populations, uncovering the diversity and population structure. The study also revealed the differences in the prevalence of tsetse flies and associated trypanosomosis across the native tracts of Burkinabe taurine cattle populations had shaped the level of zebu introgression in them.